Reliability analysis of gear-bearing drive systems considering gear manufacturing and installation errors - Jinzhou Song; Yifan Wang; Lei Hou; Tao Zhang; Minghe Zhang; Zhibin Zhang; Yifan Jiang; Yi Chen; Rongzhou Lin; Yushu Chen (Scientific Reports)
Abstract Gear-bearing drive systems often exhibit manufacturing and installation errors, which can significantly affect system performance, and longevity, and increase the probability of failures. This paper focuses on the reliability analysis of gear-bearing drive systems with uncertainties in system parameters such as gear backlash and bearing clearance, caused by gear and bearing manufacturing and installation errors. First, a dynamic model of the gear-bearing drive system, incorporating coupled dynamic meshing parameters, is established. Then, the deterministic dynamic model of the system is combined with the Chebyshev interval analysis method to develop a reliability analysis model for the gear-bearing drive system with uncertain parameters. The study analyzes the variations in system natural frequencies and vibration responses due to gear quality and initial gear and bearing clearances at different deviation rates. The results indicate that at the same rotational speed and deviation rate, the initial bearing clearance has a more significant impact on the system’s dynamic characteristics compared to the initial gear clearance. At different rotational speeds and the same deviation rate, system reliability decreases with increasing average initial interference of the bearing at low speeds. At high speeds, a large bearing clearance deviation may cause abnormal fluctuations in system vibration. This method provides a prioritization of parameter control for the structural optimization and design of gear-bearing systems.